Nondestructive testing using ultrasonic sensor - Abd Rahman, Muhamad Umar Faruq; Fazlul Rahiman, Mohd Hafiz; Abdul Rahim, Ruzairi; Ahmad, Nasarudin (Penerbit UTHM, 2016)
Nondestructive testing (NDT) is the process of inspection or evaluating materials or component without destroying the functionality, serviceability and the structure of the testing product. Therefore, after the inspection is done the testing product can still be used as usual compared to the destructive testing that can cause the damage to the testing product. In the other word destructive testing has limitation because of the technique need a sampling product rather than on the materials is already put into the service. NDT are often used to determine the properties of the materials such as strengthen ductility, porosity and toughness. Todays, NDT are widely used in industries, manufacturing, and fabrication and in service inspection to ensure the quality of the product. Besides that, NDT also can reduce production cost by minimize the damage onto the product and also can reduce the production time by without damaging the testing product. Also in construction field, there are many benefits from NDT process toward this area such as to evaluate the strength of concrete. There are many method of NDT today such as Magnetic Particle Testing, Ultrasonic Testing, and Vibration Analysis. For testing of the building basically people are used the Ultrasonic Pulse Velocity (UPV) and Rebound Hammer. This paper is specifically discussed about the Nondestructive Testing (NDT) by using Ultrasonic.